The mental health consequences of interpersonal gun violence: A systematic review - Mohammed Abba-Aji; Shaffi Fazaludeen Koya; Salma M. Abdalla; Catherine K. Ettman; Gregory Herschel Cohen; Sandro Galea (Elsevier, 2024)
Background: Gun violence is a global public health concern that has significant implications for mental health. This systematic review aims to synthesize the existing literature on the mental health consequences of interpersonal gun violence. Methods: A comprehensive search was conducted across PubMed, PsycInfo, and Web of Science databases to identify relevant studies published up to December 15, 2023. Studies were included if they documented the mental health impact of interpersonal gun violence. The data extraction process included information on study design, population characteristics, exposure to gun violence, mental health indicators, and measurement instruments. Results: A total of 58 studies were included in the review. The studies varied in design, population, and mental health indicators assessed. We found that exposure to interpersonal gun violence was significantly associated with increased reports of post-traumatic stress disorder, depressive symptoms, and substance use. We also found that interpersonal gun violence exposure was associated with increased disruptive behaviors and the likelihood of gun carrying especially among adolescents. Further, those closer to the interpersonal gun violence consistently reported more adverse mental health consequences than persons less centrally involved. The review also highlighted limitations in the current literature, including a narrow focus on certain mental health indicators and a paucity of studies from countries other than the US. Conclusion: The consequences of interpersonal gun violence extend beyond immediate physical injury to include enduring mental health impacts. This review also highlights the need for further research to better understand the impact of gun violence on mental health.